2020
DOI: 10.15829/1560-4071-2020-4061
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms of cardiac troponins: mechanisms and clinical significance

Abstract: Modern laboratory methods for determining biomarkers of cardiovascular diseases are highly sensitive and can detect almost single molecules in human biological fluids, significantly speeding up and improving the diagnosis of cardiovascular diseases. However, in this case, there is a decrease in specificity and it is necessary to take into account a number of additional factors that may affect the result of the study. Recent studies have shown that circadian rhythms (CR) are among these factors. This review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 45 publications
0
33
0
20
Order By: Relevance
“…60 Gender, age and circadian features provide quite remarkable information obtained by highly sensitive methods about the troponin biology. 61 With regard to gender characteristics, it was found that the level of cardiacspecific troponins in men is higher than in women, which is recommended to be used to determine the values of 99th percentile in modern diagnostic algorithms for the diagnosis of AMI. [62][63][64] The higher level of cardiac troponins in men is explained by the fact that they have a larger left ventricular mass than women.…”
Section: Some New Data On Troponin Biochemistry and Diagnostic Capabilities Of High-sensitivity Troponin Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…60 Gender, age and circadian features provide quite remarkable information obtained by highly sensitive methods about the troponin biology. 61 With regard to gender characteristics, it was found that the level of cardiacspecific troponins in men is higher than in women, which is recommended to be used to determine the values of 99th percentile in modern diagnostic algorithms for the diagnosis of AMI. [62][63][64] The higher level of cardiac troponins in men is explained by the fact that they have a larger left ventricular mass than women.…”
Section: Some New Data On Troponin Biochemistry and Diagnostic Capabilities Of High-sensitivity Troponin Assaysmentioning
confidence: 99%
“…70 It is noteworthy that circadian fluctuations of hs-cTnT concentrations are much more pronounced in patients with comorbid pathologies, in particular CRF and diabetes mellitus, than in healthy patients. 61 According to some reports, circadian rhythms may have a potential impact on the accuracy of early diagnosis of AMI and screening for CVD. 36 For example, hs-cTnI and hs-cTnT levels that naturally change throughout the day can be erroneously interpreted as diagnostically significant abnormalities.…”
Section: Some New Data On Troponin Biochemistry and Diagnostic Capabilities Of High-sensitivity Troponin Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Сердечно-сосудистые заболевания являются одними из ведущих причин смертности и инвалидизации населения. Лабораторная диагностика сердечнососудистых заболеваний является актуальным направлением, поскольку она является одним из ключевых методов верификации диагноза [1,2,3,4,5].…”
Section: Introductionunclassified
“…Изучение новых биомаркеров должно включать валидацию аналитической погрешности и пределов обнаружения, характеристику калибратора, специфичность и стандартизацию анализа, преаналитические вопросы и соответствующие исследования референсных интервалов [5,6,7,8,9,10]. Идеальный биомаркер должен помочь врачу в диагностике, прогнозе и лечении.…”
Section: Introductionunclassified